2015
DOI: 10.5897/ajb2014.13850
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rural processing methods and postharvest storage treatments on quality characteristics of kola nut (acuminata Schott Endl.)

Abstract: Quality changes of kola nut (Cola acuminata) as affected by processing methods and short-term storage environments were investigated. The experiment was conducted at the Teaching and Research Laboratory of the Department of Crop Science, University of Nigeria Nsukka, Nigeria. The treatments comprised of: three different colour plastic buckets -red, green, white and three inner liningsNewbouldia laevis leaves, Spondias mombin leaves and Black polyethylene sheets giving a 3 × 3 × 3 treatment combinations. The N.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Moreover, unlike leaf, which has to be changed regularly because it dries up quickly, nylon has the advantage that it does not dry up quickly and thus, does not need changing for the period the kolanut is in storage [21]. However, a study by Eze et al [22] showed that storing kolanut under modified atmosphere using botanical leaves, remarkably improved the postharvest and culinary qualities of the nuts when compared with those stored in polyethylene, which acts as the modern storage method.…”
Section: Kolanut Product Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, unlike leaf, which has to be changed regularly because it dries up quickly, nylon has the advantage that it does not dry up quickly and thus, does not need changing for the period the kolanut is in storage [21]. However, a study by Eze et al [22] showed that storing kolanut under modified atmosphere using botanical leaves, remarkably improved the postharvest and culinary qualities of the nuts when compared with those stored in polyethylene, which acts as the modern storage method.…”
Section: Kolanut Product Qualitymentioning
confidence: 99%
“…Also, the Federal Government of Nigeria is yet to accord a full export status to kolanut. This is probably as a result of the non-availability of kolanut all year round and its attack by storage pests during storage [22]. Kolanut is highly sought after because of its many usages in pharmaceuticals and soft drinks production [7].…”
Section: Kolanut Tradementioning
confidence: 99%